The Influence of Cooperative Services on the Participation of KPRI Syariah Cooperative Members of the Ministry of Religion of Pekanbaru City - Ana Ulfa Sugiarti; Makhdalena Makhdalena; Hendripides Hendripides (CV. Rayyan Dwi Bharata, 2023)
This article is a type of quantitative descriptive research that aims to determine the effect of cooperative services on the participation of members of the KPRI Syariah cooperative, Ministry of Religion, Pekanbaru City. The method used in this research is a quantitative descriptive method. The population in this study were all members of the KPRI Syariah cooperative, the Ministry of Religion, Pekanbaru City. The research sample involved 87 cooperative members using a random sampling technique. Data collection methods in this study are questionnaires, interviews and documentation. The instrument used to collect data is a questionnaire or questionnaire. The data analysis technique used the T test. Based on the obtained sig large 2.606 cooperative services, 2.200 member participation. With a significant level of 0.011 0.031. This shows that cooperative services partially have a significant effect on the participation of members of the KPRI Syariah cooperative, Ministry of Religion, Pekanbaru City.